Strain diversity and infection durations of Staphylococcus spp. and Streptococcus spp. causing intramammary infections in dairy cows - S. Woudstra; N. Wente; Y. Zhang; S. Leimbach; M.K. Gussmann; C. Kirkeby; V. Krömker (Journal of Dairy Science, 2023)
ABSTRACT: To effectively prevent and control bovine mastitis, farmers and their advisors need to take infection pathways and durations into account. Still, studies exploring both aspects through molecular epidemiology with sampling of entire dairy cow herds over longer periods are scarce. Therefore, quarter foremilk samples were collected at 14-d intervals from all lactating dairy cows (n = 263) over 18 wk in one commercial dairy herd. Quarters were considered infected with Staphylococcus aureus, Streptococcus uberis, or Streptococcus dysgalactiae when ≥100 cfu/mL of the respective pathogen was detected, or with Staphylococcus epidermidis or Staphylococcus haemolyticus when ≥500 cfu/mL of the respective pathogen was detected. All isolates of the mentioned species underwent randomly amplified polymorphic DNA (RAPD)-PCR to explore strain diversity and to distinguish ongoing from new infections. Survival analysis was used to estimate infection durations. Five different strains of Staph. aureus were isolated, and the most prevalent strain caused more than 80% of all Staph. aureus infections (n = 46). In contrast, 46 Staph. epidermidis and 69 Staph. haemolyticus strains were isolated, and none of these caused infections in more than 2 different quarters. The 3 most dominant strains of Strep. dysgalactiae (7 strains) and Strep. uberis (18 strains) caused 81% of 33 and 49% of 37 infections in total, respectively. The estimated median infection duration for Staph. aureus was 80 d, and that for Staph. epidermidis and Staph. haemolyticus was 28 and 22 d, respectively. The probability of remaining infected with Strep. dysgalactiae or Strep. uberis for more than 84 and 70 d was 58.7 and 53.5%, respectively. Staphylococcus epidermidis and Staph. haemolyticus were not transmitted contagiously and the average infection durations were short, which brings into question whether antimicrobial treatment of intramammary infections with these organisms is justified. In contrast, infections with the other 3 pathogens lasted longer and largely originated from contagious transmission.